Policy formulation and administration : a casebook of top-management problems in business - Christensen, C. Roland; Berg, Norman A.; Salter, Malcolm S. (Homewood, Ill. : R. D. Irwin, 1976)
The book provides both text and a selection of cases that can assist men and women preparing for a career in business administration to become acquainted with the opportunities and challenges confronting the top manager of a firm.
First-6th ed. by G. A. Smith, Jr. (2d-4th, with C. R. Christensen; 5th, with C. R. Christensen and N. A. Berg; 6th, with C. R. Christensen, and others.
Includes bibliographical references.
hza 27/09/2018, ijb 07/02/2019
Loans
Keywords: Industrial management